CLASSIFICATION OF HAZARD POTENTIALS AND SAFETY MAP IN KITCHEN PT. DENSO INDONESIA SUNTER PLANT - Hanifah Agda Nursitasari (Journal of Industrial Hygiene and Occupational Health, 2019)
The kitchen is a place where food processing take place. The function of company's kitchen is processing the food for workers at the company. Large-scale food processing certainly uses large-scale cooking tools such as Chopper, Boiling Pan, Rice Cooker, Oven and 6 Burner and others. The usage of equipment in food processing contain potential risk to all company residents, especially kitchen chefs who are often exposed. The purpose of this study was to classify potential hazards according to their risk level and establish a safety map as a form of hazard communication aid. The method of this research was observational and descriptive method. It was found that potential hazards in the kitchen were gas leaks and fires, cold, truncated fingers, slipping, being hit by kitchen equipment included in the category of minor hazards, while contact with heat was included in the moderate hazard category. Safety map was made in the kitchen of Pt Denso Indonesia Sunter Plan.Keyword: potential hazard; safety map; kitchen